2009
DOI: 10.1175/2009waf2222222.1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Precipitation Forecast Skill between Small Convection-Allowing and Large Convection-Parameterizing Ensembles

Abstract: 2An experiment is designed to evaluate and compare precipitation forecasts from a 5-member, 4-km grid-spacing (ENS4) and a 15-member, 20-km grid-spacing (ENS20) Weather Research and Forecasting (WRF) model ensemble, which cover a similar domain over the central United States.The ensemble forecasts are initialized at 2100 UTC on 23 different dates and cover forecast lead times up to 33 hours. Previous work has demonstrated that simulations using convection-allowing resolution (CAR; dx ~ 4-km) have a better repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
154
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(163 citation statements)
references
References 65 publications
8
154
0
1
Order By: Relevance
“…Vegetation and land-use classifications, are provided by the new IGBP-MODIS dataset containing 20 different land-use categories with a resolution of 30 . Although we operate the model with a horizontal resolution of 3.6 km, we did not use a convection parametrization, since a resolution of ∌4 km was shown to reasonably represent precipitation patterns without a convection scheme (Kain et al, 2008;Weisman et al, 2008;Clark et al, 2009).…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Vegetation and land-use classifications, are provided by the new IGBP-MODIS dataset containing 20 different land-use categories with a resolution of 30 . Although we operate the model with a horizontal resolution of 3.6 km, we did not use a convection parametrization, since a resolution of ∌4 km was shown to reasonably represent precipitation patterns without a convection scheme (Kain et al, 2008;Weisman et al, 2008;Clark et al, 2009).…”
Section: Experimental Set-upmentioning
confidence: 99%
“…They mainly focus on the investigation of the impact of CP ensemble configurations, for example, the generation of IC perturbation, representation of the model error, uncertainties from the lateral boundary conditions (LBCs), ensemble size, and spatial scale (Kong et al, 2006;Clark et al, 2009Clark et al, , 2011Bouttier et al, 2012;Ben BouallĂšgue et al, 2013;KĂŒhn-lein et al, 2014;Schwartz et al, 2015;Schumacher and Clark, 2014;Romine et al, 2014;Tennant, 2015). There are few comprehensive studies on the evaluation of CP EPS, in particular, in comparison with the mesoscale regional EPS.…”
Section: Introductionmentioning
confidence: 99%
“…There are few comprehensive studies on the evaluation of CP EPS, in particular, in comparison with the mesoscale regional EPS. Clark et al (2009) compared a 5-member 4 km grid spacing convection-permitting ensemble with a 15-member 20 km grid spacing regional ensemble. Their case studies revealed that the convection-permitting ensemble generally provided more accurate precipitation forecasts than the coarser-resolution regional EPS.…”
Section: Introductionmentioning
confidence: 99%
“…Both approaches address aspects of model uncertainty and the former approach is in common use (e.g. Clark et al, 2009;Yussouf and Stensrud, 2011;Gebhardt et al, 2011). The main goal of this study is to compare the two approaches.…”
Section: Introductionmentioning
confidence: 99%